Microbiological characteristics of perianal streptococcal dermatitis - Šterbenc, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2016)
Beta-hemolytic streptococci (BHS) are the most common causative agents of perianal streptococcal dermatitis (PSD). This study evaluates the distribution of BHS isolates in perianal bacterial cultures. We retrospectively reviewed microbiological results for perianal BHS that were isolated in our laboratory between 2006 and 2015. We identified a total of 105 BHS isolates from rectal swabs and swabs of clinically intact perianal skin. The majority of BHS were of group A (GABHS) (73/105; 69.5%), followed by group B BHS (GBBHS) (27/105; 25.7%), and non-group A or B BHS (5/105; 4.8%). The distribution of GABHS was age-specific, with the majority of GABHS obtained from young children. All BHS isolates were susceptible to penicillin. GABHS were universally suscepti - ble to clindamycin, whereas 1.4% were resistant to erythromycin. GBBHS were resistant to erythromycin and clindamycin in 14.8% and 7.4% of cases. In addition, we wanted to emphasize the importance of correct diagnosis of PSD. Hence, we provide a review of protocols that can decrease the time to diagnosis and treatment of PSD, reduce patients% discomfort, and prevent unnecessary diagnostic procedures.
Keywords: bakterijske infekcije; beta-hemolytic streptococci; diagnostika; perianal bacterial cultures; perianalni dermatitis; streptococcal dermatitis; streptokokni dermatitis